1973
DOI: 10.1136/bmj.1.5850.402
|View full text |Cite
|
Sign up to set email alerts
|

Lead Intoxication in Children in Birmingham

Abstract: concentrations of 37-60 .Lg/lOO ml, levels previously accepted as harmless.Children with blood lead concentrations greater than 60 tug/100 ml show radiological evidence of lead intoxication, and treatment for this should be considered when blood lead concentration exceeds 37 Fg/100 ml. Children presenting with unexplained encephalopathy should be radiographed for evidence of lead intoxication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 8 publications
0
19
0
5
Order By: Relevance
“…The other was labeled as 'red surma' and was in the form of red to orange powder. These powder brands from India had the highest concentration of lead and serve to explain the several cases of lead poisoning (plumbism) including one fatality among Indian and Pakistani children in England as a result of the use of lead containing kohl [8,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The other was labeled as 'red surma' and was in the form of red to orange powder. These powder brands from India had the highest concentration of lead and serve to explain the several cases of lead poisoning (plumbism) including one fatality among Indian and Pakistani children in England as a result of the use of lead containing kohl [8,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Direct toxic effects on bone metabolism may result from long-term accumulation of lead. Betts et al (39) observed changes in bone density in 93% of children whose blood lead was treater than 60 ,ug/dl and in 24% of children with blood lead between 37 and 60 ,ug/dl. Bone formation was disturbed when beagle dogs were fed low doses of lead over a 6-month period.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Snodgrass et al [11] concluded that 12 children in five families in England had high blood concentrations of lead due to the lead in the cosmetics used on them. Betts et al [12] also reported on lead poisoning in Birmingham, England resulting from the use of surma. Other investigators found higher lead levels in the blood of children in England using surma than those who do not use surma [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 94%